Influenza-like illness in residential care homes: a study of the incidence, aetiological agents, natural history and health resource utilisation. Issue 8 (4th February 2008) - Hui, D S; Woo, J; Hui, E; Foo, A; Ip, M; To, K-W; Cheuk, E S C; Lam, W-Y; Sham, A; Chan, P K S
Abstract : Background: Influenza-like illness (ILI) among elderly people living in residential care homes (RCHEs) is a common cause for hospitalisation. A study was undertaken to examine the incidence, underlying aetiology, natural history and associated healthcare resource utilisation related to ILI in the RCHE population. Methods: A prospective study of ILI in four RCHEs in Shatin, Hong Kong was conducted from April 2006 to March 2007. Each RCHE was monitored daily for the occurrence of ILI and followed up until resolution of illness or death. Clinical features were recorded and sputum, nasopharyngeal aspirate, blood and urine specimens were examined for underlying aetiology. Results: 259 episodes of ILI occurred in 194 subjects, with mild peaks in winter and summer, over a sustained level throughout the year. The infectious agent was identified in 61.4% of all episodes, comprising bacterial infection in 53.3% and viral in 46.7%. Multiple infections occurred in 16.2% of subjects. The most frequent organism was Streptococcus pneumoniae, followed by respiratory syncytial virus, Pseudomonas aeruginosa, metapneumovirus and parainfluenza virus types 1 and 3. Clinical features did not vary according to the underlying aetiology, the common presenting features being a decrease in general condition, cognitive and functional deterioration, and withholding of food in addition to fever and respiratory symptoms. Overall, mortality at 1 month/discharge was 9.7%. Infection with methicillin-resistant Staphylococcus aureus, low body mass index and poor function predisposed to mortality. No association was observed between influenza vaccination status and underlying aetiology, clinical features or outcome. Conclusions: The clinical presentation of ILI is non-specific and is mainly due to bacterial and viral infections other than influenza in the RCHE population.